"F**k Ukraine" - Candace Owens Explains Why America Should Not Support Ukraine - Valuetainment (2023)
Patrick Bet-David and Candace Owens discuss U.S. involvement in international conflicts, specifically focusing on Ukraine. Candace Owens argues why America should reconsider its stance on global interventions. ▶ PBD Podcast | EP 304 Connect With Experts On Minnect: https://app.minnect.com/ Want to get clear on your next 5 business moves? https://valuetainment.com/academy/ Join the channel to get exclusive access to perks: https://bit.ly/3Q9rSQL Download the podcasts on all your favorite platforms https://bit.ly/3sFAW4N Text: PODCAST to 310.340.1132 to get the latest updates in real time! Patrick Bet-David is the founder and CEO of Valuetainment Media. He is the author of the #1 Wall Street Journal Bestseller Your Next Five Moves (Simon & Schuster) and a father of 2 boys and 2 girls. He currently resides in Ft. Lauderdale, Florida.